Respuesta :
x x
----------------- - --------------------
x^2 -4x + 4 x^2-3x+2
x x
= ---------------- - --------------------
(x -2)^2 (x - 2)(x - 1)
x (x-1) - x(x +2)
= ----------------------------
(x -2)^2 (x - 1)
x^2 -x -x^2 - 2x
= --------------------------
(x -2)^2 (x - 1)
-3x
= -----------------------
(x -2)^2 (x - 1)
answer
missing term in the equation: -3x
----------------- - --------------------
x^2 -4x + 4 x^2-3x+2
x x
= ---------------- - --------------------
(x -2)^2 (x - 2)(x - 1)
x (x-1) - x(x +2)
= ----------------------------
(x -2)^2 (x - 1)
x^2 -x -x^2 - 2x
= --------------------------
(x -2)^2 (x - 1)
-3x
= -----------------------
(x -2)^2 (x - 1)
answer
missing term in the equation: -3x
Answer:
The missing term is x.
Step-by-step explanation:
Given expression is,
[tex]\frac{x}{x^2-4x+4}-\frac{x}{x^2-3x+2}------(1)[/tex]
Since, [tex]x^2-4x+4=(x)^2-2\times (2x)+(2)^2[/tex]
[tex]\implies x^2-4x+4=(x-2)^2------(2)[/tex] ( (a-b)² = a² - 2ab + b² )
Now, [tex]x^2-3x+2=x^2-2x-x+2[/tex] ( By middle term splitting )
[tex]=x(x-2)-1(x-2)[/tex]
[tex]\implies x^2-3x+2=(x-1)(x-2)------(3)[/tex]
From equation (1), (2) and (3),
[tex]\frac{x}{x^2-4x+4}-\frac{x}{x^2-3x+2}=\frac{x}{(x-2)^2}-\frac{x}{(x-2)(x-1)}[/tex]
[tex]=\frac{x(x-1)-x(x-2)}{(x-2)^2(x-1)}[/tex]
[tex]=\frac{x(x-1-x+2)}{(x-2)^2(x-1)}[/tex]
[tex]=\frac{x(1)}{(x-2)^2(x-1)}[/tex]
[tex]=\frac{x}{(x-2)^2(x-1)}[/tex]
Hence, the missing term in the equation is x.